Multitargeted Effects of Vitexin and Isovitexin on Diabetes Mellitus and Its Complications - Ibrahim Luru Abdulai; Samuel Kojo Kwofie; Winfred Seth Gbewonyo; Daniel Boison; Joshua Buer Puplampu; Michael Buenor Adinortey (The Scientific World Journal)
Background. Till date, there is no known antidote to cure diabetes mellitus despite the discovery and development of diverse pharmacotherapeutic agents many years ago. Technological advancement in natural product chemistry has led to the isolation of analogs of vitexin and isovitexin found in diverse bioresources. These compounds have been extensively studied to explore their pharmacological relevance in diabetes mellitus. Aim of the Study. The present review was to compile results from in vitro and in vivo studies performed with vitexin and isovitexin derivatives relating to diabetes mellitus and its complications. A systematic online literature query was executed to collect all relevant articles published up to March 2020. Results. In this piece, we have collected data and presented it in a one-stop document to support the multitargeted mechanistic actions of vitexin and isovitexin in controlling diabetes mellitus and its complications. Conclusion. Data collected hint that vitexin and isovitexin work by targeting diverse pathophysiological and metabolic pathways and molecular drug points involved in the clinical manifestations of diabetes mellitus. This is expected to provide a deeper understanding of its actions and also serve as a catapult for clinical trials and application research.